How costly is modern maritime piracy for the international community? - Inmaculada Martínez-Zarzoso; Sami Bensassi (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2010)
This paper focuses on the impact of maritime piracy on international trade. Piracy increases the cost of international maritime transport through an increase in insecurity regarding goods deliveries. Bilateral trade flows between the main European and Asian countries over the 1999 to 2008 period are used to estimate an augmented gravity model that includes various measures of piracy acts. We found robust evidence indicating that maritime piracy reduces the volume of trade; the effect of ten additional vessels hijacked being associated to an 11% decrease in exports. Using these results, the international cost of piracy in terms of trade destruction is estimated to be 28 billion dollars. Finally, we compare the cost of low intensity conflict like Somalia, to the cost of a full scale conflict (Afghanistan) and to the cost of an autarkic state (North Korea) for the international community in the year 2008.The results indicate that the cost of war more than doubles the cost of low intensity conflict.
Keywords: F10; F51; 330; piracy; international trade; gravity equation; cost of conflict; security; Schifffahrt; Kriminalität; Seeräuber; Außenwirtschaft; Soziale Kosten; Gravitationsmodell; Internationale Wirtschaftsbeziehungen; Welt; Europa; Asien